Influent Factors for the failure of IT Project Implementation And the Engineering Mindset of Project Managers - Umaji, Kittisak; Paireekreng, Worapat (Journal of Applied Statistics and Information Technology, 2023)
Due to the trend of higher investment in information technology in the recent years. As a result, there are many information technology projects occurred. However, the statistics show that more than two-thirds of the projects were unable to implement based on plan. The purposes of this research were to study the factors affecting the failure of the IT project implementation. Also, to study the relationship between the IT project implementation outcomes and the Engineering Mindset skills of project managers. These includes the study of factors affecting the development of the Project Manager’s Engineering Mindset. The samples of this survey were chosen from 214 project managers who worked in Thailand and involved in information technology projects by specific purpose technique. In the study, a questionnaire that passed the IOC reviewing process was used to survey data. The statistics used in the research were the mean average method and standard deviation (S.D.) In addition, Cronbach's alpha coefficient was used to test the confidence of the questionnaire The research findings showed that project scope management and project communication management were the two main factors that affected project failure with a combined percentage of 58.76%. The Engineering Mindset of project managers, including Adaptive Mindset, Growth Mindset and Learning Mindset, is one of the key factors that affect the success or failure of a project. It was also found that direct experience in project management is likely to be one of the key factors in the development of an engineering mindset for project managers.